Prospects and challenges in algal biotechnology - Tripathi, Bhumi Nath; Kumar, Dhananjay (Springer, 2017)
This contributed volume presents the latest research and state-of-the-art approaches in the study of microalgae. It describes in detail technologies for the cultivation of marine, freshwater and extremophilic algae, as well as phototrophic biofilms, cyanobacterial mats and periphytons, including the media requirements and growth rates of different types of algae. The second part of the book is dedicated to the biotechnological applications of algal biomass and secondary metabolites produced by these organisms, and critically discusses topics such as algae-based biofuels and CO2 sequestration. In addition, it reviews the prospects and challenges of algal bioremediation of domestic and industrial wastewaters, including the use of planktonic and self-immobilized algae systems in wastewater treatment, explaining their merits and drawbacks. Lastly, it highlights research methods and approaches related to the production of high-value products and bioactive compounds.
Keywords: Algae -- Biotechnology.; elektronické knihy; electronic books